Syngas Production via Bi-Reforming of Methane Over Fibrous KCC-1 Stabilized Ni Catalyst - Farooqi, A.S. (2022)
Bi-reforming of methane (BRM) technology has the potential to serve as an alternative energy source while also mitigating greenhouse gas emissions. However, the main hurdle in the commercialization of BRM is catalyst deactivation. In this study, the ultrasonic-assisted impregnation method was utilized to prepare a Ni-based catalyst supported on fibrous KCC-1 and tested in the BRM process. The prepared catalysts were characterized by XRD, BET, FESEM and TPR-H2 techniques to determine the textural and morphological properties of the catalyst. The catalytic performance was tested in a tabular fixed-bed continuous reactor at 800Â Â°C with a stoichiometric feed ratio of 3:2:1 for CH4: H2O: CO2. For high nickel loadings, it was discovered that agglomerates of the Ni-active phase form on the surface of the support. The catalysts with a 10 wt Ni content produced the best CO2 (79.2) and CH4 (82.1) conversions, as well as an optimum H2/CO = 1.62 ratio. Â© 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.